Pengumbaran Konflik Rumah Tangga di Media Sosial Perspektif Hukum Islam - Sakinah, Sakinah; Shavia, Andina Najma (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2024)
Abstract: Conflict in the household is inevitable, where husbands and wives often have different views. In the modern era, domestic conflicts are often no longer resolved in a closed and discreet manner but are expressed on social media or in public spaces in the form of personal stories, emotional statements, accusations, or insults. This study uses a descriptive analytical method with a literature study approach to analyse this phenomenon. The results of the study show that the disgrace of the family in public spaces or social media can damage the honour of individuals and families and have the potential to cause defamation and moral destruction of the community. Based on the Islamic law perspective, Islam teaches emotional maturity, honesty, and sincerity in resolving conflicts. In conclusion, Islam emphasised the importance of resolving problems wisely, maintaining family privacy and building harmony through a mature spiritual and emotional approachKeywords: Domestic conflicts, social media, Islamic law.Abstrak: konflik dalam rumah tangga merupakan hal yang tidak dapat dihindari, di mana suami dan istri sering memiliki pandangan yang berbeda. Di era modern, konflik rumah tangga sering kali tidak lagi diselesaikan secara tertutup dan bijaksana melainkan diungkapkan di media sosial atau ruang public dalam bentuk cerita pribadi, pernyataan emosional, tuduhan, atau penghinaan. Penelitian ini menggunakan metode deskriptif analitik dengan pendekatan studi kepustakaan untuk menganalisis fenomena tersebut. Hasil penelitian menunjukkan bahwa pengumbaran aib keluarga di ruang publik atau media sosial dapat merusak kehormatan individu dan keluarga serta berpotensi menyebabkan pencemaran nama baik dan kehancuran moral masyarakat. Dalam perspektif hukum Islam, Islam mengajarkan kedewasaan emosi, kejujuran, dan keikhlasan dalam menyelesaikan konflik. Islam menekankan pentingnya penyelesaian masalah secara bijak, menjaga privasi keluarga dan membangun keharmonisan melalui pendekatan spiritual dan emosional yang matang.Kata kunci: Konflik rumah tangga, etika, media sosial, hukum Islam.